"Giving comes before receiving": High performance wide temperature range Li-ion battery with Li5V2(PO4)3 as both cathode material and extra Li donor. (December 2019) - Song, Zihan; Feng, Kai; Zhang, Hongzhang; Guo, Peng; Jiang, Lihua; Wang, Qingsong; Zhang, Huamin; Li, Xianfeng
Abstract: The wide temperature (especially bellow −20 °C) performance of the commercial lithium ion batteries using graphite anodes have been criticized for a long time. One most possible solution is to use hard carbon (HC) as anode but its huge irreversible capacity loss (ICL) has to be compensated during initial charging process. In order to overcome this issue, we propose the Li5 V2 (PO4 )3 (L5VP) cathode to match the HC anode. Based on a "Giving comes before receiving" strategy, L5VP is firstly obtained by lithiating Li3 V2 (PO4 )3 (L3VP) as the "giving" step; Then the ICL of HC is entirely compensated by de-lithiation of L5VP below 3.0 V (vs. Li + /Li) so called "receiving". As a result, the L5VP||HC pouch full cell exhibits a much higher initial Coulombic efficiency of 96.7% and achieves a high specific energy of 320 Wh kg −1 at room temperature. Especially, it can charge and discharge at −40 °C with 80% capacity delivery, which is the best performance ever reported. In addition, over 90% energy retention can also be achieved at a high temperature of 55 °C, exhibiting wonderful wide temperature range (−40–55 °C) performance. Furthermore, the L5VP shows a stable phase transition behaviour and the minimum heat release (10–40 J g −1 ) during lithium insertion/extraction, which are studied via in-situ XRD, CV and thermal analysis methods. This work can arouse wide research interests of battery or hybrid capacitor systems with similar pre-lithiation or pre-sodiation issues. Graphical abstract: Image 1 Highlights: Li5 V2 (PO4 )3 cathode is realized to pre-lithiate hard carbon for the first time. High energy and initial Coulombic efficiency are achieved by designed full cells. Superior cell performances are obtained in wide temperature range from -40-55 °C. In-situ XRD result confirms the stability of lithiated Li5 V2 (PO4 )3 for cycling.